2008
DOI: 10.1175/2007jamc1571.1
|View full text |Cite
|
Sign up to set email alerts
|

Model Calculations of Solar Spectral Irradiance in the 3.7-μm Band for Earth Remote Sensing Applications

Abstract: Since the launch of the first Advanced Very High Resolution Radiometer (AVHRR) instrument aboard the Television and Infrared Observational Satellite (TIROS-N), measurements in the 3.7-m atmospheric window have been exploited for use in cloud detection and screening, cloud thermodynamic phase and surface snow/ice discrimination, and quantitative cloud particle size retrievals. The utility of the band has led to the incorporation of similar channels on a number of existing satellite imagers and future operationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
1
18
0
2
Order By: Relevance
“…Given the slightly different nature of the 3.7 µm channel in that it includes a thermal component and has no on board measurement of downwelling solar irradiance it is plausible that these factors result in a difference in retrieval bias. Platnick and Fontenla (2008) highlighted the uncertainties involved in estimating the solar irradiance in the 3.7 µm channel given the lack of available observations and showed that using different estimations of this quantity can result in around a 5 % shift in r e retrievals. A shift of this order for instance could significantly change the relationship between r 2.1 and r 3.7 examined in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the slightly different nature of the 3.7 µm channel in that it includes a thermal component and has no on board measurement of downwelling solar irradiance it is plausible that these factors result in a difference in retrieval bias. Platnick and Fontenla (2008) highlighted the uncertainties involved in estimating the solar irradiance in the 3.7 µm channel given the lack of available observations and showed that using different estimations of this quantity can result in around a 5 % shift in r e retrievals. A shift of this order for instance could significantly change the relationship between r 2.1 and r 3.7 examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Using an optimal estimation technique the thermal and solar components do not need to be separated, instead a surface temperature and temperature profile is used by the forward model to include thermal contributions to simulated measurements. In order to model the solar component of the radiance a reference value of the top of atmosphere solar irradiance is calculated from the parametrisation of Platnick and Fontenla (2008) and used as input to the forward model.…”
Section: N J King Et Al: Evaluating Modis Cloud Retrievals 203mentioning
confidence: 99%
“…Reconstructions of solar UV irradiance based on NLTE spectral synthesis of radiance spectra have also being progressing. Besides, first encouraging tests of the models have been carried out in the IR (Fontenla et al 2006;Platnick and Fontenla 2008;Unruh et al 2008). More work is still needed in these directions.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, in order to reduce a local variation and remove noise, a low pass filter (LPF) was applied to three different maps [31]. LPF, implemented in ArcMap software, calculates the average (mean) value for each 3 × 3 neighbourhood.…”
Section: Application Of the Stumpf Methodsmentioning
confidence: 99%
“…The values of band-averaged solar spectral irradiance used for the Atmospheric Correction (AC) are reported in Table 3 [31].…”
Section: Pre-processing Satellite Wv-3 Datamentioning
confidence: 99%